2005
DOI: 10.1007/s10493-005-0508-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Beauveria bassiana and Metarhizium anisopliae to the tobacco spider mite Tetranychus evansi

Abstract: Seventeen isolates of Metarhizium anisopliae (Metschnikoff) Sorokin and two isolates of Beauveria bassiana (Balsamo) Vuillemin were evaluated for their pathogenicity against the tobacco spider mite, Tetranychus evansi Baker & Pritchard. In the laboratory all the fungal isolates were pathogenic to the adult female mites, causing mortality between 22.1 and 82.6%. Isolates causing more than 70% mortality were subjected to dose-response mortality bioassays. The lethal concentration causing 50% mortality (LC5o) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 19 publications
6
49
2
3
Order By: Relevance
“…Kanga et al (2002) obtained CL90 for V. destructor of 1.37 x 10 9 conidia mL -1 of an M. anisopliae isolate on day 7 post inoculation, which was higher than that obtained in this trial. For other mite species like Tetranychus evansi, Wekesa et al (2005) point out a lethal concentration between 0.7 x 10 7 and 2.3 x 10 7 conidia mL -1 to achieve the 50% mortality with diverse M. anisopliae isolates, values that are again higher than those found in our trials.…”
Section: Laboratory Trialscontrasting
confidence: 64%
“…Kanga et al (2002) obtained CL90 for V. destructor of 1.37 x 10 9 conidia mL -1 of an M. anisopliae isolate on day 7 post inoculation, which was higher than that obtained in this trial. For other mite species like Tetranychus evansi, Wekesa et al (2005) point out a lethal concentration between 0.7 x 10 7 and 2.3 x 10 7 conidia mL -1 to achieve the 50% mortality with diverse M. anisopliae isolates, values that are again higher than those found in our trials.…”
Section: Laboratory Trialscontrasting
confidence: 64%
“…Fries (=Paecilomyces farinosus), Hirsutella thompsonii Fisher, and Neozygites floridana Weiser and Muma often play an important role in decreasing native populations of phytophagous mites (Chandler et al, 2000;Van der Geest et al, 2000). Searching for microbial control agents in laboratory experiments it has been shown that some of the tested isolates of B. bassiana and M. anisopliae are highly virulent to the active stages of T. urticae (Alves et al, 2002a;Tamai et al, 2002;Chandler et al, 2005) and T. evansi Baker and Pritchard (Wekesa et al, 2005). According to Feng (2006, 2009) some of the tested isolates of B. bassiana, Paecilomyces fumosoroseus (Wize) Brown and Smith and M. anisopliae have high lethal effect on eggs and females of T. urticae.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for such methods, natural enemies are being evaluated as biological control agents of T. evansi (Wekesa et al 2005, Furtado et al 2007, Brito et al 2009. Another strategy that has been used where conventional pesticides are not allowed, such as in ecological and organic production systems, is the use of non synthetic products for pest control (Campanhola & Bettiol 2003, Venzon et al 2008a.…”
mentioning
confidence: 99%